Analysis of The Quality of Public Services In The Manufacture of Identity Cards (KTP) In The Department of Population and Civil Registration of The City of Majalengka - Oxy Hendro Prabowo (Journal of Business Social and Technology, 2020)
Public service is the most highlighted thing in any government organization that provides services. One of the public services provided is the making of Identity Card (KTP), as one of the services provided by the government. In this service, the community becomes the most important assessor in knowing the extent of the quality of public services provided by government officials. This paper aims to find out the extent of the quality of public services carried out by the government apparatus to the community. The background of doing this writing is because in terms of the quality of public services, the government apparatus as the implementation of public services is considered less optimal in serving the community. Karna felt less optimal because it takes a long time in the manufacture. The method of writing used is to use qualitative methods through descriptive approaches, by taking the location of writing in the Civil Registration and Population Office of the City of Majalengka, while the key informants in this writing are the Head of the Population and Civil Registration Office of the City of Majalengka, and the Head of Population Coming Field, then the Community on site as the main assessor in the services provided. The data sources used in this writing are primary data and secondary data. The primary data in this writing is obtained from the results of polling and interviews, while secondary data is obtained from other libraries to support the data that has been obtained. Data collection methods used are literature studies, observations, and in-depth interviews. Data analysis is done through data reduction, data display, data verification and inference. In this study the authors used the dimensions of Public Service in Lovelock theory to measure the extent of the quality of public service. The result is (1) Tangible: not optimal enough, (2) Realiable: not enough oprimal, (3) Responsiveness: optimal enough, (4) Assurance: not optimal enough, (5) Empathy: not optimal enough. From the research that researchers did about the Quality of Public Services in the Making of Identity Cards (KTP) in the Office of Population and Civil Registration of the City of Majalengka, it can be concluded that it has not run optimally. Because it takes a long time in the making, which is not in accordance with the promise given by the government.